The Roman Inquisition, the Index and the Jews: contexts, sources and perspectives - Wendehorst, Stephan (Studies in European Judaism 1568-5004, 2010)
"The present volume deals with the relations between the Catholic Church, Jews and Judaism and the potential of the now accessible sources in the archive of the Congregation for the Doctrine of the Faith in Rome for throwing new light on this intricate relationship."--BOOK JACKET.Title Summary field provided by Blackwell North America, Inc. All Rights Reserved